The Death of Kedis Cangak for Its Greedy (Function And Values Analysis) - Ni Made Suarningsih; I Nyoman Suwija; I Ketut Suar Adnyana; Anak Agung Gede Putera Semadi; I Gusti Agung Laksmi Swaryputri (Mimbar Ilmu, 2023)
Balinese society is affluent in oral literature, among which there are satua or Balinese folk tales. Recently, it has been felt that the Masatua tradition has declined dramatically. The increasingly busy level of parents causes this. Entertainment on social media has defeated oral traditions. This research aims to analyze the function and value of the  Death of Kedis Cangak for Its Greedy. This study uses a qualitative method. The data collection method for this research is the observation method using reading and note-taking techniques. The research results were analyzed using analytical descriptive methods and presented using informal processes. The research analysis uses the matching process. The research results show that the functions of the "Death of Kedis Cangak for Its Greedy" unit are entertainment, educational, and social sanctions or punishment functions. Values analysis, which focuses on religious values, found values such as tattwa (philosophy) and moral values (ethics). There is an entertainment function, an educational function, and a social sanction or punishment function. Values such as tattwa (philosophy) and moral values (ethics) are found in value analysis, which focuses on religious matters. Regarding philosophical issues, we found the application of the karma phala law, one of the Panca Sradha teachings. The law of karma befalls the character I Kedis Cangak. The value of morals is also reflected in the behavior of the main character, which is contrary to the teachings of morals.